Risk factors for injury in rugby union football in New Zealand: a cohort study. Issue 2 (21st December 2011) - Chalmers, David J; Samaranayaka, Ari; Gulliver, Pauline; McNoe, Bronwen
Abstract : Objective: To identify risk factors for injury in amateur club rugby. Design: Prospective cohort design; with follow-up over the 2004 season. Setting: Amateur club rugby in New Zealand. Participants: Seven hundred and four male rugby players, aged 13 years and over. Assessment of risk factors: The study investigated the independent effect on injury incidence of age, ethnicity, rugby experience, height, weight, body mass index, physical activity, cigarette smoking, previous injury, playing while injured, grade, position, training, time of season, warm-up, foul play, weather conditions, ground conditions and protective equipment. Generalised Poisson regression was used to estimate the effect of each factor after adjusting for all other factors. Main outcome measures: Game injury, defined as 'any event that resulted in an injury requiring medical attention or causing a player to miss at least one scheduled game or team practice'. Results: A total of 704 players, representing 6263 player-games, contributed information on injury and exposure. Evidence was obtained of the effect on injury incidence of increasing age, Pacific Island versus Maori ethnicity (injury rate ratio (IRR)=1.48, 1.03–2.13), ≥40 h strenuous physical activity per week (IRR=1.54, 1.11–2.15), playing while injured (IRR=1.46, 1.20–1.79), very hard ground condition (IRR=1.50, 1.13–2.00), foul-play (IRR=1.87, 1.54–2.27) and use of headgear (IRR=1.23, 1.00–1.50). Conclusions: Opportunities for injury prevention might include promoting injury-prevention measures more vigorously among players of Pacific Island ethnicity, ensuring injured players are fully rehabilitated before returning to play, reducing the effects of ground hardness through ground preparation and stricter enforcement of the laws relating to foul play.